2019
DOI: 10.1148/radiol.2018180887
|View full text |Cite
|
Sign up to set email alerts
|

Chest Radiographs in Congestive Heart Failure: Visualizing Neural Network Learning

Abstract: To examine Generative Visual Rationales (GVRs) as a tool for visualizing neural network learning of chest radiograph features in congestive heart failure (CHF). Materials and Methods: A total of 103 489 frontal chest radiographs in 46 712 patients acquired from January 1, 2007, to December 31, 2016, were divided into a labeled data set (with B-type natriuretic peptide [BNP] result as a marker of CHF) and unlabeled data set (without BNP result). A generative model was trained on the unlabeled data set, and a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 13 publications
0
66
0
1
Order By: Relevance
“…Previous studies have used other deep learning methods, with variable results in detecting cardiomegaly but also using a smaller sample size (36)(37)(38)(39). Another study has tested 3 transfer learning algorithms including Inception 3 but found out much lower accuracy levels than the ones we describe here (40).…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have used other deep learning methods, with variable results in detecting cardiomegaly but also using a smaller sample size (36)(37)(38)(39). Another study has tested 3 transfer learning algorithms including Inception 3 but found out much lower accuracy levels than the ones we describe here (40).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, our developed GANs can be used to visualize what the generator neural network sees and to reveal correlations between diseases. This might be used in several ways: as a check that the GAN has been trained correctly, as a tool to uncover relationships between diseases or to visualize hallmark changes of pathologies [37] and potentially also as a decision support system for diagnosis. Another advantage of the proposed concept of data sharing is the immense reduction in data storage requirements: storing of a single radiograph image with a resolution of 1024 × 1024 and a bit depth of 8 bits requires 1 megabyte of hard drive space.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the ‘black-box’ nature of DL algorithms since it is often unclear what information is used to come to a certain classification or result. Techniques to visualize salient features can potentially help address this limitation [88]. Furthermore, the present lack of model robustness and lack of portability with respect to different CMR scanners, sequences, imaging parameters and institutions need to be addressed.…”
Section: Barriers To Implementationmentioning
confidence: 99%